The use of mobile phones in the public areas of a Nigerian University Library (2011)
Mobile phones are important means of communication but its use is becoming incessant and considered distractive by some library users. A questionnaire was designed for a survey to elicit the reactions of library users on how best to handle its usage in Kenneth Dike Library (KDL), University of Ibadan, Nigeria. 1,500 copies were placed at the reference and circulation sections of the library for users to complete. Of the total number of questionnaires made available, 1,290 copies, representing 86%, were returned. These were analyzed using frequency, percentages and inferences. 1,010 (78.29%) of the respondents affirm that they are distracted each time a cell phone rings near them in the library. It is therefore suggested, among other things, that the university authority (employing its official organs and enlisting the support of the students’ union) should come up with appropriate rules and regulations on the use of mobile phones in the library while the library should provide designated areas where calls could be made and/or received within its premises with appropriate notices and instructions posted in conspicuous areas. In addition, users should be encouraged to put their global system of mobile communication (GSM) handsets in the vibration/silent modes whenever they are in the library